Modifications in transformer design to reduce temperature rise - Chong, Siew Wei (Universiti Malaysia Sarawak, UNIMAS, 2009)
An ideal transformer is one which has no losses. This would entail having purely inductive coils wound on a loss-less core, impossible to realize in practice. Transformer losses are dissipated as heat, leading to higher operating temperatures which cause the transformer insulating materials to deteriorate faster. If there is a breakdown of the insulation system, transformer will fail. This research identifies causes of the heat generation from the windings and magnetic core of a transformer in operation, and methods of reducing this from the aspects of design, materials used and workmanship during manufacturing of transformer. It is also covers how this heat can be removed effectively through proper arrangement of cooling ducts, selection of good transformer oil as the agent for heat removal, and optimal designs of transformer tank and fin walls for efficient heat dissipation to the surrounding medium.